Sex-based performance differences in shot put, javelin, and long jump among U.S. youth athletes aged 10 years and under - Brown, G. A.; Shaw, B. S.; Shaw, I. (The Journal of Strength and Conditioning Research, 2026)
Controversy currently exists over whether sex-based differences necessitate sex-segregated youth sports. This study examined sex-based performance differences in shot put, javelin throw, and long jump among athletes aged 10 years and under using data from USA Track & Field (USATF) Regional Junior Olympic Championships. Performance records from all 15 USATF regions for the 2022, 2023, and 2024 Regional Junior Olympic Championships were analyzed. Distances recorded in shot put, javelin throw, and long jump for male and female athletes in the 8-and-under and 9-10-year-old age groups were compared using 2-sample t-tests (p < 0.05). Hedges' g was calculated to determine effect sizes. Percentile analyses (10th-95th) were also conducted for each sex and event. Males significantly outperformed females in all 3 events across both age groups (p < 0.0001). Effect sizes were large for javelin (Hedges' g = 1.138 and 1.099) and shot put (g = 0.730 and 0.741), and medium for long jump (g = 0.429 and 0.473). Male performance advantages ranged from 8 to 55% depending on event and age group. Percentile analyses revealed consistent male advantages across the entire performance distribution, suggesting inherent sex-based trends regardless of ability level. These findings demonstrate clear sex-based performance differences in throwing and jumping events among prepubertal athletes. Although physical activity levels may contribute to these differences, anatomical and physiological factors likely play a significant role. Coaches, parents, and sport governing bodies should consider these sex-based performance trends when developing training programs, setting expectations, and establishing age-group competition structures for youth athletes.